Financial Auditing Facilitating High-Quality Development in the Insurance Industry: Theoretical Logic and Realistic Challenges in the New Internet Era - Wang, Zihan (Journal of Global Economy, Business and Finance, 2025)
This paper studies the impact of financial auditing on the insurance industry. First, it explains the meaning of financial auditing and its role in maintaining economic and financial security, promoting policy implementation, preventing and controlling risks, combating financial violations and improving regulatory effectiveness; secondly, it analyzes the differences and connections between Internet insurance and traditional insurance in terms of insurance channels, product design, cost prices, service models, etc.; then it discusses the necessity of conducting financial auditing in the context of the new era, and the importance of conducting financial auditing in the insurance industry to safeguard the nature of insurance companies, promote their development and improve the industry regulatory system; finally, it points out that current financial auditing faces problems such as incomplete scope and the need to improve personnel quality, as well as legal and regulatory risks, product risks, and information security risks in the Internet insurance industry, and proposes corresponding risk control countermeasures, aiming to provide theoretical and practical references for financial auditing to enable high-quality development of the insurance industry.